Predictive Maintenance of Compressor Using ThingSpeak IoT Platform (International Journal of Scientific Research and Management (IJSRM), 2021)
Any instrument or machine that needs to be monitored and inspected on a regular basis to ensure its long life and proper maintenance. Machine condition monitoring in the time and frequency domain is unquestionably required to ensure reliability. Condition monitoring is a method of observing a machine’s condition parameter (vibration, temperature and etc.), with the explicit objective of detecting a substantial change that could indicate the onset of a malfunction It’s an important part of compressor predictive maintenance and lowering compressor downtime. In today’s world, the Internet of Things (IoT) is the most effective approach and technology for continuously monitoring the state of any machine. We’ve employed MEMS sensors to detect misalignment, non-linearity, and other anomalies., Through the Wi-Fi module ESP8266, vibrations and temperature in compressors, as well as changes in signals, will be communicated to the cloud. These signals are in order in the temporal domain. The Fast Fourier transform is used to examine and convert the time domain sequence into the frequency domain.